POLICIES FOR ROTATING AND PROMOTING EMPLOYEES TO INCREASE WORK MOTIVATION AND THE IMPLICATIONS FOR EMPLOYEE PERFORMANCE - Maman Suratman (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2022)
Employee performance in a company is the result of the quality and quantity of the work achieved by employees in carrying out their duties in accordance with the responsibilities given to them. Performance does not always meet expectations. Motivation is one of the determinants of good performance. Employee motivation can be influenced by several factors including promotion and rotation of employees. The purpose of this study is to determine the effect of rotation and promotion policies on work motivation and the implications for employee performance. The research method used is descriptive verification. The units of analysis are permanent employees of the Tirta Intan Regional Drinking Water Company (Perusahaan Daerah Air Minum Tirtamarta) in Garut Regency. The determination of the sample was carried out by using the sampling percentage table as proposed by Yount (1999). Data collection was carried out with a questionnaire and through observations. The statistical tests in this study used correlation and regression analysis. The results of the f-test show that the three variables (job rotation, promotion, and work motivation) simultaneously affect employee performance. The partial T-test results show that each variable (job rotation and promotion) has an effect on work motivation, and work motivation has an effect on employee performance.